2015 2nd International Conference on Information and Communication Technologies for Disaster Management (ICT-DM) 2015
DOI: 10.1109/ict-dm.2015.7402058
|View full text |Cite
|
Sign up to set email alerts
|

Pulling Information from social media in the aftermath of unpredictable disasters

Abstract: Social media have become a primary communication channel among people and are continuously overwhelmed by huge volumes of User Generated Content. This is especially true in the aftermath of unpredictable disasters, when users report facts, descriptions and photos of the unfolding event. This material contains actionable information that can greatly help rescuers to achieve a better response to crises, but its volume and variety render manual processing unfeasible. This paper reports the experience we gained fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…For example, while a minority (15%) of AARs reported using data analysis technologies during disaster response, newer types of these technologies now exist, such as those using artificial intelligence and machine learning (AI/ML), which have the potential to autonomously ingest, analyze, generate anomaly alerts, and make inferences and conclusions about large volumes of data in real time. Examples included ML analysis of social media posts to detect and localize an incident 59,145,172 and machine vision-based detection of anomalies, such as fire, and prediction about the severity of disaster damage. 175,177 If implemented, AI/ML has the potential to revolutionize SA during disaster response operations.…”
Section: Figurementioning
confidence: 99%
“…For example, while a minority (15%) of AARs reported using data analysis technologies during disaster response, newer types of these technologies now exist, such as those using artificial intelligence and machine learning (AI/ML), which have the potential to autonomously ingest, analyze, generate anomaly alerts, and make inferences and conclusions about large volumes of data in real time. Examples included ML analysis of social media posts to detect and localize an incident 59,145,172 and machine vision-based detection of anomalies, such as fire, and prediction about the severity of disaster damage. 175,177 If implemented, AI/ML has the potential to revolutionize SA during disaster response operations.…”
Section: Figurementioning
confidence: 99%
“…More recently, the use of "tweets" (short messages on online social media platform Twitter 1 ) assisted in providing more realtime information on the geographical region of the "news" where the earthquake took place and the amount of structural damage caused (Earle et al, 2010(Earle et al, , 2012Sakaki et al, 2010;Liang et al, 2013;Avvenuti et al, 2015;Bossu et al, 2015;Hicks, 2019). Panagiotou et al (2016) noticed a relationship between the time Twitter users tweeted and the time the event took place, highlighting the importance of social media users acting as news collaborators.…”
Section: Introductionmentioning
confidence: 99%
“…Liang et al (2013) analyzed how fast the news spread over a period of 90 minutes and managed to identify a correlation between retweet densities and tweeting count per user versus the distance from the earthquake's epicenter. Similarly, Avvenuti et al (2015) studied the relationship between the earthquake's magnitude and how tweets are spread around the geographical area hit by the earthquake. They took into consideration unique Twitter users and the mean value of tweets submitted following the earthquake event.…”
Section: Introductionmentioning
confidence: 99%
“…This limitation drastically reduces the number of useful messages and results in very sparse maps. Recent work have instead demonstrated that emergency reports frequently carry textual references to locations and places [3,4], as shown in Fig. 1.…”
Section: Introductionmentioning
confidence: 99%
“…http://en.wikipedia.org/wiki/2012 Northern Italy earthquakes 4. http://www.reuters.com/article/2012/05/20/us-quake-italy-idUSBRE84J01K20120520.…”
mentioning
confidence: 99%